Modal Psikologi Terhadap Peak Perfomance - Fitriana Pujarina; Anisia Kumala (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2019)
Indonesia is one of the countries that have great potential in the paralympic Olympics or sports for athletes with disabilities. Through the 2018 Asian Para Games held in Jakarta in October, proving the achievements of our athletes, Indonesia ranked fifth in this event. Therefore the purpose of this study was to determine the effect of Psychological Capital on Peak Performance in disabled athletes. This research method uses a quantitative approach. Respondents in this study consisted of 50 athletes with disabilities. The results of this study are to see the validity and reliability test using the Cronbach Alpha formula with an Alpha coefficient of 0.913 on the Psychological Capital scale and 0.92 on the Peak Performance scale. Data analysis in this study used a simple regression analysis technique with SPSS. The results of this study indicate that there is a significant influence between Psychological Capital on Peak Performance (R Square coefficient (R2) of 0.258 and probability value of 0,000). This means that the higher the Psychology Capital, the higher the Peak Performance of disabled athletes. The contribution of Psychological Capital to peak performance was 25.8%.